Reflections on Native-Newcomer Relations : Selected Essays - Miller, J. R. (James Rodger), 1943- (Book collections on Project MUSE., 2004)
The twelve essays that make up Reflections on Native-Newcomer Relations illustrate the development in thought by one of Canada's leading scholars in the field of Native history - J.R. Miller. The collection, comprising pieces that were written over a period spanning nearly two decades, deals with the evolution of historical writing on First Nations and Métis, methodological issues in the writing of Native-newcomer history, policy matters including residential schools, and linkages between the study of Native-newcomer relations and academic governance and curricular matters. Half of the essays appear here in print for the first time, and all use archival, published, and oral history evidence to throw light on Native-Newcomer relations.Miller argues that the nature of the relationship between Native peoples and newcomers in Canada has varied over time, based on the reasons the two parties have had for interacting. The relationship deteriorates into attempts to control and coerce Natives during periods in which newcomers do not perceive them as directly useful, and it improves when the two parties have positive reasons for cooperation. Reflections on Native-Newcomer Relations opens up for discussion a series of issues in Native-newcomer history. It addresses all the trends in the discipline of the past two decades and never shies from showing their contradictions, as well as those in the author's own thinking as he matured as a scholar.